2020
DOI: 10.3389/fcell.2020.00077
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Coordination of Pericyte Phenotypes: Therapeutic Implications

Abstract: Pericytes are mural vascular cells found predominantly on the abluminal wall of capillaries, where they contribute to the maintenance of capillary structural integrity and vascular permeability. Generally quiescent cells in the adult, pericyte activation and proliferation occur during both physiological and pathological vascular and tissue remodeling. A considerable body of research indicates that pericytes possess attributes of a multipotent adult stem cell, as they are capable of self-renewal as well as comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 189 publications
(218 reference statements)
2
43
0
Order By: Relevance
“…The involvement of EPCs could be possible given their ability for homing and further differentiation ( Kioi et al, 2010 ; Wei et al, 2019 ). Moreover, endothelial cells could be also generated during neovascularization by trans-differentiation from mesenchymal cells ( Balaji et al, 2013 ) and/or from pericytes ( Nwadozi et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The involvement of EPCs could be possible given their ability for homing and further differentiation ( Kioi et al, 2010 ; Wei et al, 2019 ). Moreover, endothelial cells could be also generated during neovascularization by trans-differentiation from mesenchymal cells ( Balaji et al, 2013 ) and/or from pericytes ( Nwadozi et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ligand, released from angiogenic endothelial cells, binds to its receptor PDGFRB expressed by developing pericytes. [ 1 , 36 , 37 ]…”
Section: Vascular Systemmentioning
confidence: 99%
“…[ 27 ] Studies have shown that pericytes are dominantly quiescent in established blood vessel networks, but can proliferate and differentiate into progenitor cells, when said network is being remodeled. [ 37 ] They have been shown to differentiate into a vast array of lineages, including those of mesenchymal and neural stem cells. [ 36 , 37 ] Interestingly, in the adult brain, pericytes have been found directly adjacent to the tip cells of elongating blood vessels, suggesting a crosstalk between the two cell types in the CNS.…”
Section: Vascular Systemmentioning
confidence: 99%
“…There are many similarities in metabolism shifts with PC phenotype compared to MSCs and microglia. 71,72 For these cells, glycolysis is associated with more primitive phenotype, while the lineage-committed differentiation uses more oxidative phosphorylation, showing the upregulation of mitochondrial capacity. [73][74][75][76][77] In particular, Notch signaling is involved in the regulation of PC metabolism and quiescence, for example, through the downregulation of glycolytic enzymes (e.g., PFKFB3).…”
Section: Metabolic Regulation Of Pc Phenotypementioning
confidence: 99%
“…Hyperglycemia elevates flux through the hexosamine pathway, and increased levels of fatty acids result in insulin resistance and lipid toxicity. 71…”
Section: Metabolic Regulation Of Pc Phenotypementioning
confidence: 99%